Back in Europe and adjusting to the new realities of the 1990's in Hungary. - Bigler, Robert M. (East European Quarterly)
Most of the recent attention about Hungary has focused on the results of the May 1994 parliamentary elections and on the change of government from the center-right Democratic Forum that had ruled since 1990 to the social-liberal government led by former communist foreign minister Gyula Horn, current leader of the Socialist Party. The impact of poor economic conditions and voter dissatisfaction with the economic performance of the Democratic Forum government has been emphasized. However, few observers discuss the remarkable stability of the new democracy in a country that has little experience in the functioning of a free democratic system or the smooth and orderly transition from one government to another as the result of free democratic elections. This transition amounts to a confirmation of the efficient functioning of postcommunist Hungary's new constitutional regime. If Horn's coalition can hold power and stabilize the economy, and if it can continue integrating Hungary into the European Union, there is reasonable hope for slow improvement.